Reclassification and weighting of multiple causes of death: US death certificates 2003–2023 - Michael Levitt; Ben Marten; Gal Oren; John P. A. Ioannidis (Proceedings of the National Academy of Sciences, 2026)
Death certificates record causes of death as reported by certifiers (Entity Axis) and as standardized by mortality coding rules (Record Axis). Conventional statistics reduce these to a single underlying cause, ignoring other contributing conditions; weighting schemes can instead distribute the burden across all listed causes. We evaluated reclassification from Entity to Record axis and weighting across all 56,986,831 US death certificates from 2003 to 2023, mapping International Classification of Diseases (ICD)-10 codes to 14 broad disease categories and testing three weighting schemes: W1 (50% to the underlying cause, 50% shared equally among contributing causes), W2 (equal weighting across all causes), and W2A (equal weighting at the ICD-10 code level). Entity and Record Axes agreed on underlying cause in 48,313,403 deaths (84.8%) by broad category and 39,260,709 deaths (68.9%) by ICD-10 code ( SI Appendix , Table S5 A and B ); concordance reached 70.4% using 3-character. Reclassification markedly increased COVID-19 (+92%) and Transport deaths (+43%) while decreasing Other External Causes (−54%). Weighting substantially altered burden attribution: COVID-19 (−44 to –63%) and Falls (−46 to –66%) decreased, Other External causes more than tripled (+204 to 254%), and deviations from unweighted counts were more pronounced with W2 and W2A than W1. Weighting also brought disease-category counts closer to Entity Axis values and restored Respiratory seasonality suppressed during the pandemic. Systematic differences between reported and reclassified causes of death, and the choice of weighting scheme, profoundly alter disease burden estimates for several causes, with major implications for resource allocation and public health priorities.